Analisis Tingkat Metakognisi Peserta Didik dalam Memecahkan Masalah Matematika - Nopyta Intan Sari; Amrullah Amrullah; Syahrul Azmi; Ketut Sarjana (Pendidikan Matematika FKIP Universitas Mataram, 2021)
Metacognition is the students awareness about their thought processes and monitoring their thought processes. One of thought processes which referred is problem solving ability. In problem-solving the students were different levels of metacognition. Level of metacognition consists of tacit use, aware use, strategic use, dan reflektive use. The purpose of this study was to determine the level of metacognition of students in solving problems and the relationship between mathematical problem solving abilities and the level of metacognition. The research was conducted by giving test instruments to 23 sample students. This research was a descriptive research with qualitative and quantitative approaches. Qualitative data analysis used flow models method with the stages of data reduction, data presentation and drawing conclusions. Furthermore, quantitative data analysis used spearman rank correlation. After the data analysis process, the results of the research were metacognition level of class IX students consisting of tacit use, aware use, and strategic use with percentages of 80%, 15%, and 5%. Furthermore, relationship between problem solving ability and the level of metacognition are in the very high category with a correlation coefficient of 0.68. Therefore, when the problem-solving ability increases, the level of metacognition also increases.